Factors Associated With The Level Of Self-Confidence In Using Computer Technology Among Teachers Of English Language In Schools In Kota Bharu District, Kelantan - Wan Nazihah, Wan Mohamed (2002)

(untitled)
The purpose of this study was to determine whether selected factors were associated with the level of self-confidence in using computer technology among teachers of the English language in Kota Bharu district schools. The selected variables investigated were age, gender, formal education level, years of teaching experience, computer usage, amount of computer experience, computer training background, place of attending computer training and mode of attending computer training. A survey instrument was mailed to a sample of secondary school English teachers within Kota Bharu district. Of the 142 instruments mailed, 112 usable surveys were returned for 78.9% return rate. The primary statistical procedures used in testing the hypotheses in this study were t-tests. Conclusions drawn from the study were (1) none of the selected socio-demographic variables is significantly related to the English teachers' level of self-confidence in using computer technology; (2) both computer usage and amount of computer experience variables are significantly related to the English teachers' level of self-confidence in using computer technology; (3) computer training background variable is significantly related to the level of self-confidence among the English teachers; and (4) several types of computer technology applications that the English teachers felt confident in using them are word processing progams, the Internet, spreadsheet programs, and telecommunication system.